Integrated Electrical Resistivity Tomography and SPAC Microtremor for Local Site Response Assessment toward Sustainable Disaster Risk Reduction: A Case Study of Setiling Village, Central Lombok - Syarifatul Ulfah; Muhamad Yamin; Bagus Widhi Dharma S. (Jurnal Penelitian Pendidikan IPA, 2026)
Local geological conditions strongly influence seismic-wave propagation and earthquake ground response, particularly in heterogeneous volcanic environments. This study aimed to characterize shallow subsurface conditions and assess local seismic site response in Setiling Village, Central Lombok, Indonesia, by integrating two-dimensional Electrical Resistivity Tomography (ERT) using the Wenner–Schlumberger configuration with Spatial Autocorrelation (SPAC)-based microtremor analysis. Three ERT profiles and twenty SPAC measurement points were acquired to evaluate subsurface heterogeneity and near-surface stiffness. The ERT results revealed significant resistivity variations associated with volcanic lithology, weathering intensity, moisture content, and groundwater conditions. Conductive zones (<100 Ωm) were interpreted as highly weathered volcanic deposits, whereas higher resistivity zones (>600 Ωm) represented relatively competent volcanic materials. SPAC-derived Vs30 values ranged from 150 to 525 m/s, corresponding to NEHRP Site Classes C, D, and E. Integrated interpretation demonstrated a consistent relationship between resistivity and Vs30, indicating that progressive volcanic weathering simultaneously reduces electrical resistivity and subsurface stiffness. The integrated ERT–SPAC approach provides a reliable framework for village-scale seismic site characterization, supporting seismic hazard assessment, risk-informed spatial planning, resilient infrastructure development, and disaster risk reduction in tropical volcanic regions.